ASSESSMENT OF MARKET SEGMENTATION AND PERCEIVED SALES VOLUME OF TOYOTAAND HONDA VEHICLE PRODUCTS IN NIGERIA - UMUNNA CAJETAN (International Studies Journal)
The study looked into the effect of the market on a company's product or service sales volume. Market segmentation is critical for any company striving to compete in the global marketplace. Consumer needs are varied, and they must all be satisfied as efficiently as feasible. As a result, companies that provide a product or service must understand their numerous target customers and segment their products appropriately for each area. This research examines the segmentation process and how it may be used to increase the sales volume of an organization's goods or services. Trend analysis was utilized to assess data collected from both primary and secondary sources. According to the findings, once products or services are adapted to various sorts of consumer segments, the criteria will be met, resulting in satisfaction and increased demand for that product or service. The study suggests that successful consumer segmentation can boost an organization's demand for a product or service. It has also been suggested that if a profit-making corporation wants to improve sales, they should always work around segmenting customers of their product or service.